RNA-based fluorescent biosensors for live cell imaging of small molecules and RNAs. (June 2020) - Su, Yichi; Hammond, Ming C
Graphical abstract: Highlights: Palette of fluorogenic RNA-dye pairs now are available for biosensor engineering. RNA-based fluorescent biosensors developed for molecular imaging applications. RNA-based fluorescent biosensors developed for imaging native RNAs. Abstract : Genetically encodable fluorescent biosensors provide spatiotemporal information on their target analytes in a label-free manner, which has enabled the study of cell biology and signaling in living cells. Over the past three decades, fueled by the development of a wide palette of fluorescent proteins, protein-based fluorescent biosensors against a broad array of targets have been developed. Recently, with the development of fluorogenic RNA aptamer-dye pairs that function in live cells, RNA-based fluorescent (RBF) biosensors have emerged as a complementary class of biosensors. Here we review the current state-of-the-art for fluorogenic RNA aptamers and RBF biosensors for imaging small molecules and RNAs, and highlight some emerging opportunities.